KEPENTINGAN AUSTRALIA BEKERJA SAMA DENGAN JEPANG DALAM JAPAN-AUSTRALIA ECONOMIC PARTNERSHIP AGREEMENT (JAEPA) - Dominikus Adventino Saputra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Australia and Japan have established cooperation in the economic sector, named Japan-Australia Economic Partnership Agreement (JAEPA), the purpose of this collaboration is to increase the economic growth of the two countries, in order to create justice and equity for every citizen in every country. This Agreement also facilitates easier access to investment, social, technology and education so as to strengthen cooperation between the two countries. Relations between Australia and Japan were a priority for Australian foreign policy from the 1980s to 1990s, partly because of their proximity to the United States. Since China has become a country that has a large political and economic power in Asia, Japan has increasingly strengthened the relationship with Australia. This study uses the theory of international cooperation. Cooperation between Australia and Japan is focused on the concept of a free trade area. For collecting data, this study used the document analysis method. By using this method, the author will explain how Australia's interest in Japan is in an effort to maximize the benefits of exporting its top commodities through the JapanAustralia Economic Partnership Agreement (JAEPA) in 2015. The results of this study shows that Australia make a economic cooperation with Japan in the Japan-Australia Economic Partnership Agreement (JAEPA) because top commodities from Australia such as meat, milk and grape fruit will receive reduced import duties to the Japanese market so that they can compete with other competitors. The trade export value of these top commodities tends to fluctuate due to the gradual reduction in tariffs and not all commodities receive direct tariff reductions. Keywords: Australia, Commodities, Economic Improvement, Japan, International cooperation, Japan-Australia Economic Partnership Agreement (JAEPA)